Secondary Osteosarcoma of Pelvic Bone: Long-Term Complication of Bladder Cancer Radiotherapy - Prasad, K Siva; Bala, Stalin; Ravichandran, Ambalathandi; Sadashivudu, Gundeti (Indian Journal of Medical and Paediatric Oncology, 2019)
Second cancer in the irradiated area is one of the complication of radiotherapy of which bone and soft tissue sarcomas predominate. Radiation-induced osteosarcoma (RIOS)accounts for 3.4%–5.5% of all osteosarcoma cases. A 70-year old male presented with complaints of swelling and pain in left gluteal region without any antecedent trauma. On clinical examination 8 × 8 cm size swelling palpable in left gluteal region arising form left iliac bone. He had history of bladder carcinoma 20 years ago for which he received concurrent chemoradiation. CT scan showed a large, erosive and lytic lesion of left iliac bone and biopsy of the lesion was suggestive of osteosarcoma. In view of extensive lesion eroding left half of pelvic bone, surgery was not done, and chemotherapy was planned.
Keywords: Pelvic bone; Radiotherapy; secondary osteosarcoma